Quaternary Earth-science and Palaeolithic conservation initiatives in the Tejo (Tagus), Portugal: Comparison with the Lower Thames, UK - Cunha, Pedro Proença (2023)
Geoconservation measures in the River Tejo, the Portuguese reach of the Tagus, are compared with those in the Thames downstream of London (UK). Both are fluvio-estuarine reaches with staircases of Pleistocene depositional terraces, each with important sedimentary, palaeontological and archaeological records. In both rivers, conservation measures are in place that aim to protect these records, promote research and inform the public. Inevitably there are differences in approach. Whereas Thames Quaternary interests are protected by a network of British statutory site designations, outreach is to the fore in the Tejo. Contrasting examples are highlighted here. The Tejo has interpretativematerials in localmuseums and detailed explanatory displays at the low-terrace archaeo-geological site of Foz do Enxarrique, near the border with Spain, and at other sites. The Thames, in contrast, has few examples of physical outreach provision and limited formal protection for Pleistocene archaeological material outside the geological network, although extensive informal protection is provided by interaction between local geological groups and county and local-authority administrations. There is also a considerable difference in the degree of threat,with the Tejo above Lisbon being a relatively undeveloped valley, albeitwith sporadic quarrying for aggregate, whereas the Lower Thames is an established area for infrastructure development, lying to the east of London, close to the river crossing of the orbital motorway. The different climate in the two regions profoundly influences the longevity of exposures in Quaternary deposits, with significant implications for management strategies. The comparison exercise reveals that each region would benefit from greater development of approaches used more prominently in the other; outreach measures in the Portuguese style would greatly enhance some of the Thames sites, but formal designation of Tejo exposures could prevent damaging operations being undertaken by ownerswho lack knowledge of their value, as exemplified by a case study of sites at Alpiarça, ~130 km upstream from Lisbon